Principles of clinical pharmacology - Atkinson, Arthur J., Jr. (San Diego, Calif. : Elsevier, 2012)
Principles of Clinical Pharmacology is a successful survey covering the pharmacologic principles underlying the individualization of patient therapy and contemporary drug development. This essential reference continues to focus on the basics of clinical pharmacology for the development, evaluation, and clinical use of pharmaceutical products while also addressing the most recent advances in the field. Written by leading experts in academia, industry, clinical and regulatory settings, the third edition has been thoroughly updated to provide readers with an ideal reference covering the wide range of important topics impacting clinical pharmacology as the discipline plays an increasingly significant role in drug development and regulatory science. Includes new chapters on imaging and the pharmacogenetic basis of adverse drug reactions. Offers an expanded regulatory section that addresses US and international issues and guidelines. Provides extended coverage of earlier chapters on transporters, pharmacogenetics and biomarkers and also illustrates the impact of gender on drug response. Presents a broadened discussion of clinical trials from Phase 1 to incorporate Phases II and III.
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Includes bibliographical references and index.
Mode of access: Internet
Keywords: Clinical pharmacology; Clinical pharmacology; Pharmacology, Clinical; Pharmacy; Electronic books